Sosialisasi Peran Victimologi Sebagai Ilmu Pengetahuan Dalam Penanganan Korban Tindak Pidana Pemerkosaan - Siahaan, Ade Yuliany; F, Fitriani; Novita, Rini (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
The term victimology comes from the words victim and logos (science), in Latin victimology, derived from the word victima which means victim and logos which means science. In terminology, victimology means a study of victims, the causes of victims and the consequences of victims who are human problems as a social reality. Crime typology can be viewed from two dimensions, first: from the perspective of the level of victim involvement in the occurrence of crime, second: the factors that cause a person to become a victim of crime. The suffering experienced by victims includes violence to the body and life, loss of property, and psychological disruption due to the actions of the perpetrator of the crime. In certain cases, victims can be categorized as perpetrators of crime. Victims and the role of victimology in criminal offenses have legal protection, especially rape, being one of the main focuses. Although relations such as human rights laws have affirmed the right to restitution for victims, the implementation is still not optimal in depth regarding the fulfillment of restitution rights, as well as identifying factors that cause rape. The victim factor plays an important role in being able to overcome or resolve this rape case, this requires courage from the victim to report the incident to the police.